Understanding dynamic complexity in context—Enriching contextual analysis in implementation science from a constructivist perspective - Mielke, Juliane; De Geest, Sabina; Zúñiga, Franziska; Brunkert, Thekla; Zullig, Leah L.; Pfadenhauer, Lisa M.; Staudacher, Sandra (Frontiers in Health Services, 2022)
Context in implementation science includes not only characteristics of a setting in which an intervention will be delivered, but also social systems (e.g., interrelationships). Context is dynamic and interacts with both, the intervention and its implementation. Therefore, contextual analysis is recognized as an indispensable part of implementation science methodology: it provides the foundation for successful and sustainable implementation projects. Yet, driven by the prevailing post-positivist understanding of context, contextual analysis typically focuses on individual characteristics of context. I.e., contextual dynamics and interactions go unnoticed. Conducting contextual analysis from a constructivist perspective promotes a multilayered approach, building a more comprehensive understanding of context, and thus facilitating successful implementation. In this artiucle, we highlight the limitations of prevailing perspectives on context and approaches to contextual analysis. We then describe how contextual analysis can be enriched by working from a constructivist perspective. We finish with a discussion of the methodological and practical implications the proposed changes would entail. Emerging literature attempts to address both the concept of context and methods for contextual analysis. Various theories, models and frameworks consider context, however, many of these are reductionistic and do not acknowledge the dynamic nature of context or interactions within it. To complement recent conceptualizations of context, we suggest consider the following five constructivist concepts: 1) social space; 2) social place; 3) agency; 4) sensation; and 5) embodiment. We demonstrate the value of these concepts using COVID-19 vaccination uptake as an example and integrate the concepts in the Context and Implementation of Complex Interventions (CICI) framework—an implementation science framework that pays ample attention to context. To study context from a constructivist perspective, we also suggest additional considerations in view of methodologies for data collection and analysis, e.g., rapid ethnographic methods. A constructivist perspective contributes to a stronger conceptualization of contextual analysis. Considering the five constructivist concepts helps to overcome contextual analysis' current shortcomings, while revealing complex dynamics that usually go unnoticed. Thus, more comprehensive understanding of context can be developed to inform subsequent phases of an implementation project, thereby maximizing an intervention's uptake and sustainability.